The Development and Content of the Vocational Advice Intervention and Training Package for the Study of Work and Pain (SWAP) Trial (ISRCTN 52269669) - Sowden, G.; Main, C. J.; van der Windt, D. A.; Burton, K.; Wynne-Jones, G. (Journal of occupational rehabilitation, 2019)
Purpose There are substantial costs associated with sickness absence and struggling at work however existing services in the UK are largely restricted to those absent from work for greater than 6 months. This paper details the development of an early Vocational Advice Intervention (VAI) for adult primary care consulters who were struggling at work or absent due to musculoskeletal pain, and the structure and content of the training and mentoring package developed to equip the Vocational Advisors (VAs) to deliver the VAI, as part of the Study of Work and Pain (SWAP) cluster randomised trial. Methods In order to develop the intervention, we conducted a best-evidence literature review, summarised evidence from developmental studies and consulted with stakeholders. Results A novel early access, brief VAI was developed consisting of case management and stepped care (three steps), using the Psychosocial Flags Framework to identify and overcome obstacles associated with the health-work interface. Four healthcare practitioners were recruited to deliver the VAI; three physiotherapists and one nurse (all vocational advice was actually delivered by the three physiotherapists). They received training in the VA role during a 4-day course, with a refresher day 3 months later, along with monthly group mentoring sessions. Conclusions The process of development was sufficient to develop the VAI and associated training package. The evidence underpinning the VAI was drawn from an international perspective and key components of the VAI have the potential to be applied to other settings or countries, although this has yet to be tested.